2011
DOI: 10.1111/j.1471-0528.2011.03029.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester ductus venosus screening for cardiac defects: a meta‐analysis

Abstract: Background Heart defects are the most common congenital abnormalities.Objective We aimed to evaluate in a meta-analysis the screening performance of abnormal ductus venosus (DV) Doppler waveform for detection of congenital heart disease (CHD) in chromosomally normal fetuses.Search strategy Studies were retrieved from a search of MEDLINE, ISI, SCOPUS and EMBASE (from 1999 to March 2011) using the keywords 'ductus venosus', 'DV', 'chromosomal abnormalities', 'congenital heart disease' and 'nuchal translucency'. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 35 publications
1
54
0
4
Order By: Relevance
“…126 In a meta-analysis, euploid fetuses with NT at or above the 95th percentile and abnormal ductus venosus flow had a 15% incidence of major heart malformations. 76 When NT was at or above the ≥99th percentile, the incidence increased to ≈20%. 127 This indicates that the addition of ductus venosus Doppler analysis is useful for identifying those at greatest risk among the high-risk screening population.…”
mentioning
confidence: 99%
“…126 In a meta-analysis, euploid fetuses with NT at or above the 95th percentile and abnormal ductus venosus flow had a 15% incidence of major heart malformations. 76 When NT was at or above the ≥99th percentile, the incidence increased to ≈20%. 127 This indicates that the addition of ductus venosus Doppler analysis is useful for identifying those at greatest risk among the high-risk screening population.…”
mentioning
confidence: 99%
“…During the meta-analysis conducted by Rachel and Rachael (2014), 7 completed studies were included regardless of NT status, 9 studies with increased NT were included and 7 studies with normal NT were included, and the summary revealed that sensitivity of abnormalities for TR and DV flow in the detection of CHDs were 50%, 93%, 83% while the specificity was 19%, 80% and 96% respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…Waveform analysis of the ductus venosus reduces the false-positive rate of the screening test [139,140]. For example, in fetuses with increased NT but with normal karyotype, from 11 to 13 6/7 weeks, absent or reversed A-wave (atrial contraction) in the ductus venosus is associated with a threefold increase in the likelihood of a major cardiac defect, whereas normal ductal flow is associated with a 50 % reduction in the risk for such defects [141][142][143]. It is clear that Doppler is an important tool to study fetal health in early (and late) pregnancy [130] but appropriate precautions need to be taken to limit exposure in terms of clear indication, time and acoustic output [144].…”
Section: Is Doppler Different and Can It Have Detrimental Effects On mentioning
confidence: 99%